Supramolecular Compartmentalized Hydrogels via Polydopamine Particle-Stabilized Water-in-Water Emulsions - Zhang, Jianrui (Langmuir, 2019)
[Image: see text] Compartmentalized hydrogels constitute a significant research area, for example, for catalytic and biomedical applications. As presented here, a generic method is used for compartmentalization of supramolecular hydrogels by using water-in-water emulsions based on aqueous two-phase systems. By forming the supramolecular hydrogel throughout the continuous phase of all-aqueous emulsions, distinct, microcompartmentalized materials were created. The basis for the presented compartmentalized water-in-water hydrogels is polydopamine particle-stabilized water-in-water emulsions from dextran and poly(ethylene glycol) (PEG). Addition of α-cyclodextrin (α-CD) led to supramolecular complexation with PEG and subsequent hydrogel formation showing no signs of creaming. Due to the supramolecular nature of the compartmentalized hydrogels, selective network cleavage could be induced via competing guest addition, while keeping the emulsion substructure intact.